Safety conscious or living dangerously: what is the ‘right’ level of plant photoprotection for fitness and productivity? - Murchie, Erik H. (Wiley, 2017)
Due to their sessile nature, plants could be perceived to be relatively slow and rather un-reactive. However, a plant scientist will tell you that the inability to run away (tropism notwithstanding) actually demands a highly sophisticated physiological response to the environment. Light presents an extreme case: cloud cover and wind-induced motion can lead to irradiance changes of several orders of magnitude over timescales of seconds and minutes. Being autotrophic organisms and having evolved to harvest light, plants need to dynamically regulate their biochemistry so that it operates efficiently during these fluxes, maintaining plant fitness but minimising the risk of damage.